Evaluation of the zootechnical additive SUBTILPROBIO® C-31 on feeding of laying hens in a commercial production unit - Milián, Grethel; Rodríguez, Marlén; Dias, Damarys; Rondón, Ana I.; Pérez, M. L.; Bocourt, R.; Portilla, Yadileiny; Beruvides, A. (Cuban Journal of Agricultural Science, 2019)
This study was conducted in a farm belonging to the Combinado Avícola de Matanzas, Cuba, using Leghorn L33 line laying hens, and lasted three months. The objetive of this study was to evaluate the zootechnical additive SUBTILPROBIO® for feeding laying hens. This additive was produced with strains of Bacillus subtilis, subtilis C-31 subspecies, in a concentration of 109 endospores/g. The experiment was conducted according to a completely randomized design, with two treatments: group I, base diet (maize-soybean) and group II: base diet + SUBTILPROBIO® C-31. An amount of 600 hens, with a mean weight of 1,192 grams and 113 days old was used, divided into 300 hens/treatment. Hens were located in cages under similar conditions of management and feeding. In order to determine the probiotic effect of this zootechnical additive, liveweight, intake, conversion, total production of eggs and cracked eggs, and total disqualified eggs, as well as mortality, death by pecking, cannibalism and viability were evaluated. Results showed that hens consumed the zootechnical additive had a higher increase of productive indicators like liveweight (1640.0g/1585.0g), intake (10780 kg-1 DM), conversion (1.92/2.10), egg production (15,540/15,397), cracked eggs (1,092/1,114) and disqualified eggs (69/76) for P<0.01 regarding control group. In other indicators like mortality (1/4), viability (99.6/98.6 %) and death by pecking/cannibalism (1/2), there are no differences among treatments. Results of this research demonstrate feasibility of the use of this zootechnical additive as improver of productive and health indicators for this category. Key words: zootechnical additives, endospores of Bacillus subtilis, laying hens, eggs